Keterlibatan Paru pada Demam Berdarah Dengue: Edema Paru, Efusi Pleura hingga ARDS - Nanda Juwita Amir; R. Merlinda Veronica (Pusat Riset dan Inovasi Nasional, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in tropical countries. In addition to hemorrhagic manifestations and shock, pulmonary involvement represents an important complication contributing to increased morbidity and mortality. This article aims to review pulmonary involvement in DHF based on a narrative literature review, including pleural effusion, pulmonary edema, and Acute Respiratory Distress Syndrome (ARDS). Based on the synthesis of the literature, pulmonary involvement in DHF is primarily associated with plasma leakage resulting from endothelial dysfunction and a systemic inflammatory response. Pleural effusion is the most common manifestation, reflecting increased capillary permeability, whereas non-cardiogenic pulmonary edema and ARDS occur in more severe cases due to alveolar-capillary injury. Clinical manifestations such as dyspnea, hypoxemia, and bilateral infiltrates on chest imaging require comprehensive evaluation to differentiate between cardiogenic and non-cardiogenic etiologies. Management emphasizes rational fluid therapy and lung-protective ventilation strategies in cases of ARDS. A comprehensive understanding of pulmonary involvement in DHF is essential to enhance clinical vigilance and improve patient outcomes, particularly in severe dengue cases requiring intensive cae.